Industrial power needs in Bangladesh: A fuzzy MCDM analysis of captive versus grid solutions - Sujan Banik; Iftheker Ahmed Khan; AKM Monjur Morshed; Md. Ziaur Rahman Khan; Md Aman Uddin (Results in Engineering)
The industrial sector’s rapid expansion in Bangladesh has led to a sharp increase in energy demand, necessitating reliable, cost-effective and environmentally sustainable energy solutions. Captive power plants, once key for reliable energy, may diminish their role as governments push for greater grid reliance amid concerns over depleting natural gas resources. Understanding the preference between grid and captive power plants is crucial for sustainable industrial growth in Bangladesh. This study examines these preferences using the fuzzy analytical hierarchy process (FAHP) to compare grid and captive power plants based on four primary decision criteria: economic, technical, social, and environmental along with sixteen associated sub-criteria. The results revealed that power supply from the captive power plants is preferred over grid power plants with the economic criterion being the most influential, followed by the technical, environmental, and social criteria. Among the sub-criteria, energy security, cost of electricity, reliability, and resource depletion emerged as the top priorities. Overall, the results indicated that both power sources offer unique advantages, such as grid power offering benefits like lower initial investment, shorter payback, and reduced environmental impact: while captive power is valued for enhanced reliability and stability. The novelty of this work lies in delineating the factors guiding the choice between grid and captive options in Bangladesh’s industrial sectors rather than emphasizing which one is preferred over the other. With fluctuating energy costs and rising natural gas tariffs, these insights will offer practical solutions to industry leaders and policymakers in refining energy strategies to ensure sustainable growth.